Dampak Fatherless Terhadap Perkembangan Aktivitas Sosial Anak Usia Dini Di KB-RA Bina Mutiara Hati - Putri, vara Riskita; Khorida Filasofa, Lilif Muallifatul (Jurusan PIAUD UIN Siber Syekh Nurjati Cirebon, 2025)
The background of this study is based on empirical evidence showing that the presence of fathers supports the development of children's social skills through behavioral examples and emotional support. This study aims to analyze the impact of father absence on children's social interactions at KB-RA Bina Mutiara Hati. This study uses a qualitative research method, with data collected through interviews, documentation, and participant observation of two fatherless children (ages 4 and 6): Child A and Child B, over a period of 4 weeks. Thematic analysis focused on group participation, toy sharing, and peer interactions. The results of this study show that Child A, with the support of his father through regular visits, virtual communication, and the availability of substitute support, exhibited high social activity, such as initiating group play, sharing toys, and leading interactions. Child B, without substitute support, exhibited low social activity, social anxiety such as withdrawal, and avoidance of participation. This study concludes that the absence of a father does not always have a negative impact if alternative support is available; however, without such support, the risk of social isolation increases. This study recommends family interventions to support the social development of young children.